2012
DOI: 10.2340/00015555-1320
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic Skin Excoriations: Diagnostic Criteria, Semiological Analysis and Psychiatric Profiles

Abstract: Psychogenic excoriations are also called neurotic excoriations, dermatillomania or skin picking syndrome. We proposed diagnostic criteria and then performed a study of the psychiatric profiles of outpatients with psychogenic excoriations and the circumstances around the creation of these excoriations. Although the results must be interpreted with caution because the study was performed with only 10 patients, interesting data is provided about the onset of psychogenic excoriations, the behaviour of picking, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 17 publications
4
32
0
Order By: Relevance
“…In their study conducted on 57 patients, Snorrason et al (21) demonstrated that all patients with NE are diagnosed with at least one Axis I condition during their lifetime and that depression and anxiety are the most frequently observed comorbidities. Misery et al (22) also reported that NE is closely associated with major depression and anxiety disorders.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In their study conducted on 57 patients, Snorrason et al (21) demonstrated that all patients with NE are diagnosed with at least one Axis I condition during their lifetime and that depression and anxiety are the most frequently observed comorbidities. Misery et al (22) also reported that NE is closely associated with major depression and anxiety disorders.…”
Section: Discussionmentioning
confidence: 96%
“…While certain authors classify NE within the spectrum of obsessive-compulsive disorders, other authors associate it with impulse control disorders (3,22). Arnold has suggested a classification based on compulsive, impulsive, and mixed subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with linear prurigo normally do not deny their scratching (as in malingering or factitious disorders). In linear prurigo, the scratching behaviour is usually not compulsive or impulsive, in most patients it is a reaction to chronic pruritus, while in skin picking and related SISL the respective behaviour is executed without severe pruritus . Therefore, underlying pruritus is essential in the pathophysiology of linear prurigo.…”
Section: Discussionmentioning
confidence: 99%
“…In linear prurigo, the scratching behaviour is usually not compulsive or impulsive, in most patients it is a reaction to chronic pruritus, while in skin picking and related SISL the respective behaviour is executed without severe pruritus. 6,7 Therefore, underlying pruritus is essential in the pathophysiology of linear prurigo. Of course in some patients with pruritus (and also with linear prurigo), the scratching can develop into an obsessive, compulsive or impulsive behaviour, which they regularly execute even when no itch is present.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: Skin picking has been reported in Parkinson's disease (PD) as dermatillomania, an impulsive behavior, 1 or as a delusion of parasitosis. Skin picking is commonly linked to dopamine agonist treatment of PD 2 and leads to tissue damage and, subsequently, medical complications and psychological distress.…”
mentioning
confidence: 99%